The Design and Development of an Embodied Semi-Autonomous Mentoring Intelligence (SAMI) for Use in Virtual Reality Interventions, Operationalized for the Self-Management of Chronic Pain - Bartlett, J.; Fisher, E.; Liikkanen, S.; Turunen, J.; Skog, M.; Eccleston, C. (Frontiers in Virtual Reality, 2022)
Introduction: Avatars are becoming more common in virtual reality, used as a guide, teacher, companion, or mentor through immersive experiences. Special attention needs to be paid to their design to ensure credibility and working alliance, to allow for the optimal delivery of behavior change content. Methods: We present a new embodied Semi-Autonomous Mentoring Intelligence (SAMI) avatar used in an immersive virtual reality intervention for the self-management of chronic pain. We discuss the research findings that were taken into consideration and guided the design and development of SAMI, such methods to promote working alliance with non-human agents, optimal characteristics of non-human agents, and features of effective ‘automation’. Conclusion: We provide a table of considerations and recommendations for researchers involved in designing future virtual reality characters. We provide suggestions on how future research could advance SAMI further for use in pain management and related interventions.